Effects of foliar application of zinc and boron on the yield of tomato: Zinc and Boron foliar application effects on tomato - Mahmud, N U; Salahin, N; Roknuzzaman; Kobir , M S; Ahammad, K U (Bangladesh Journal of Agriculture, 2026)
Zinc and Boron deficiencies in Bangladeshi soil is remarkable which is a major cause of yield loss of tomato. However, foliar spray of these micronutrients can be a cure of this problem. Field experiments were carried out during Rabi season of 2021-2022, 2022-2023 and 2023-2024 to evaluate the effect of foliar application of zinc (Zn) and boron (B) on the yield and yield attributes of tomato (var. BARI Tomato-21). Treatments included various combinations of Zn and B application at 300 ppm and 600 ppm. The experiment followed a Randomized Complete Block Design (RCBD) with three replications. The Zn and B were sprayed three times at 20, 40 and 60 days after transplanting (DAT). The treatment T8, containing 600 ppm Zn and 300 ppm B foliar application showed the most significant impact on plant height (140.5 cm), number of branches per plant (3.23), number of fruits per plant (54.1), individual fruit weight (56.6 g) and marketable fruit yield (101.4, 88.8 and 91.3 t ha-1, respectively in 2021-2022, 2022-2023 & 2023-2024 cropping years). Over the span of three years, the T8 treatment consistently outperformed other Zn-B combinations individual Zn or B application and the control in terms of fruit yield. Bangladesh J. Agri. 2025, 50(2): 20-29